VALIDITAS MEDIA KOMIK BERBASIS KEARIFAN LOKAL SEBAGAI SOLUSI PENDUKUNG MINAT BELAJAR IPAS - Azna Wulandari; Siregar, Nasyariah; Sayuti Nainggolan , Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This development research was motivated by the low learning interest of students and the limited use of contextual learning media based on local wisdom in Natural and Social Sciences (IPAS) learning. This study aims to examine the validity of a local wisdom-based comic learning media as a solution to support students’ learning interest in IPAS. The comic was developed using the Canva Design application and integrates Jambi local wisdom, particularly traditional medicine from the Kerinci Regency community, with fifth-grade IPAS material on the human digestive system. The research employed the Research and Development (R&D) method using the PLOMP development model, which includes preliminary investigation, design, realization, test, evaluation, revision, and implementation stages. Data were obtained through expert validation involving three validators consisting of media, material, and language experts. Data analysis was conducted using descriptive qualitative and quantitative techniques. The results showed that the comic learning media achieved a validity score of 77.7% for language aspects (valid category), 91.81% for material aspects (very valid category), and 90.47% for media aspects (very valid category). These results indicate that the local wisdom-based comic media is feasible and valid to be used as a learning media and can serve as a solution to support students’ learning interest in IPAS learning at the elementary school level.